The European Genome-phenome Archive in 2021. Issue Volume 50:Issue D1(2022) (17th November 2021) - Freeberg, Mallory Ann; Fromont, Lauren A; D'Altri, Teresa; Romero, Anna Foix; Ciges, Jorge Izquierdo; Jene, Aina; Kerry, Giselle; Moldes, Mauricio; Ariosa, Roberto; Bahena, Silvia; Barrowdale, Daniel; Barbero, Marcos Casado; et al.
Abstract: The European Genome-phenome Archive (EGA - https://ega-archive.org/ ) is a resource for long term secure archiving of all types of potentially identifiable genetic, phenotypic, and clinical data resulting from biomedical research projects. Its mission is to foster hosted data reuse, enable reproducibility, and accelerate biomedical and translational research in line with the FAIR principles. Launched in 2008, the EGA has grown quickly, currently archiving over 4, 500 studies from nearly one thousand institutions. The EGA operates a distributed data access model in which requests are made to the data controller, not to the EGA, therefore, the submitter keeps control on who has access to the data and under which conditions. Given the size and value of data hosted, the EGA is constantly improving its value chain, that is, how the EGA can contribute to enhancing the value of human health data by facilitating its submission, discovery, access, and distribution, as well as leading the design and implementation of standards and methods necessary to deliver the value chain. The EGA has become a key GA4GH Driver Project, leading multiple development efforts and implementing new standards and tools, and has been appointed as an ELIXIR Core Data Resource. Graphical Abstract: